A recent history of Australian crime prevention. Issue 4 (November 2016) - Clancey, Garner; Fisher, Daren; Yeung, Natalie
Abstract Australia has three tiers of government – Federal, State (or Territory), and Local. A document study of crime prevention arrangements in Australia was undertaken to take stock of some recent crime prevention developments within these three tiers of government. This review revealed that in recent years State and Territory crime prevention bureaux have been folded into policing agencies in some jurisdictions (Western Australia and South Australia), while in others they have had a resurgence (Victoria). All States and Territories have embraced crime prevention through environmental design ('CPTED') in some form, mostly through the development of specific planning guidelines. All Australian capital city councils (local government) actively pursue crime prevention, with diverse situational and social initiatives routinely operating in these locations. Together, these findings suggest that commitment to crime prevention remains strong among Australian capital city governments, while State and Territory crime prevention bureaux have suffered mixed fates in recent years.